Pengaruh Profitabilitas, Likuiditas Dan Leverage Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2022-2024) - Febri Nur Hidayat; Muhammad Hasan Ma'ruf; Indra Lila Kusuma (CV. Denasya Smart Publisher, 2025)
This study aims to determine the effect of profitability, liquidity, and leverage on the value of manufacturing companies in the food and beverage sub-sector of the goods and consumer industry listed on the IDX in 2022-2024. This study uses a descriptive research type with a quantitative approach. The population of this study includes 66 food and beverage sub-sector manufacturing companies listed on the IDX for the 2022-2024 period. The sampling technique used is the purposive sampling method for 20 companies. The data source for this study uses secondary data. The data collection method was obtained from the Indonesian Stock Exchange (IDX). This study uses data analysis methods, namely descriptive statistical tests, classical assumption tests, and hypothesis testing, including multiple linear regression analysis, F tests, t tests, and coefficients of determination R Square. The results of this study indicate that profitability and liquidity have a significant positive effect, while leverage has a significant negative effect.